2003
DOI: 10.2337/diabetes.52.10.2546
|View full text |Cite
|
Sign up to set email alerts
|

Low Plasma Ghrelin Is Associated With Insulin Resistance, Hypertension, and the Prevalence of Type 2 Diabetes

Abstract: Experimental studies have suggested that ghrelin plays a role in glucose homeostasis and in the regulation of blood pressure (BP). We therefore assessed the hypothesis that a low ghrelin concentration may be a risk factor for type 2 diabetes and hypertension. We also characterized the effect of the ghrelin Arg51Gln and Leu72Met mutations on ghrelin concentrations in the population-based hypertensive (n ‫؍‬ 519) and control (n ‫؍‬ 526) cohorts of our OPERA (Oulu Project Elucidating Risk of Atherosclerosis) stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
222
8
8

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 463 publications
(265 citation statements)
references
References 52 publications
27
222
8
8
Order By: Relevance
“…Obese subjects with the Arg51Gln variant had lower body weights than obese subjects with the wild-type Arg51Arg variant (Ukkola et al, 2001). Although studies A c c e p t e d M a n u s c r i p t 13 have showed correlation between Arg51Gln and lower ghrelin levels (Poykko et al, 2003;Ukkola et al, 2002), another study was unable to confirm this finding (Vivenza et al, 2004).…”
Section: Common Genetic Variations Of Ghrl and Ghs-r Genes In Human Omentioning
confidence: 97%
“…Obese subjects with the Arg51Gln variant had lower body weights than obese subjects with the wild-type Arg51Arg variant (Ukkola et al, 2001). Although studies A c c e p t e d M a n u s c r i p t 13 have showed correlation between Arg51Gln and lower ghrelin levels (Poykko et al, 2003;Ukkola et al, 2002), another study was unable to confirm this finding (Vivenza et al, 2004).…”
Section: Common Genetic Variations Of Ghrl and Ghs-r Genes In Human Omentioning
confidence: 97%
“…This study suggests that, in parallel to the situation in man,10, 11, 12, 18, 19 serum ghrelin is suppressed in cats with HS‐induced DM and in cats with DM unrelated to HS. Serum ghrelin is therefore not useful as a diagnostic for determining the presence or absence of HS in the diabetic cat.…”
Section: Discussionsupporting
confidence: 52%
“…In addition, ghrelin may be a useful treatment for diabetes. Recently, circulating ghrelin levels were discovered to be decreased in patients with type 2 diabetes [37]. Ghrelin activity is involved in insulin resistance as well as the maintenance of energy balance [37].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, circulating ghrelin levels were discovered to be decreased in patients with type 2 diabetes [37]. Ghrelin activity is involved in insulin resistance as well as the maintenance of energy balance [37]. As multiple studies have demonstrated the importance of ghrelin in glucose and insulin metabolism [2,3], ghrelin will be an important molecule to investigate the pathophysiology of diabetes.…”
Section: Discussionmentioning
confidence: 99%